Valorization of Ulva lactuca Green Seaweed as a Functional Seasoning Ingredient: From Marine Biomass to Food Innovation - I Ketut Sumandiarsa; Ni Putu Tantri Miranti; Niken Dharmayanti; Ni Made Airanthi K Widjaja Adhi; Mufti Hatur Rahmi; Rahmat Yuliandri; Desry Natalia Manuhutu; I Made Aditya Nugraha (Faculty of Fisheries and Marine Universitas Airlangga, 2026)
Graphical Abstract Highlight Research 1. A natural functional seasoning was successfully developed from Ulva lactuca without synthetic additives. 2. The seasoning demonstrated high nutritional value, including 8.67% protein, 20.78% dietary fiber, and 59.21% carbohydrates. 3. Amino acid profiling revealed exceptionally high levels of L-glutamic acid and L-aspartic acid, enhancing natural umami flavor. 4. Phytochemical screening confirmed the presence of antioxidant-rich compounds such as flavonoids, phenolics, saponins, and alkaloids. 5. Heavy metal, microbiological, and color analyses demonstrated compliance with food safety standards and strong pigment stability. 6. Shelf-life testing showed product stability up to 9.23 months in metallocene packaging, with high sensory acceptability on potato-based snacks. Abstract Seaweeds have gained increasing attention as natural food ingredients due to their nutritional value, potential to replace synthetic additives, and environmental sustainability. However, the utilization of Ulva lactuca as a natural functional seasoning remains limited, particularly regarding safety assurance, sensory acceptance, and product shelf stability. This study aimed to evaluate the potential of U. lactuca as a natural functional seasoning by assessing its nutritional composition, safety, sensory properties, and storage stability. Samples were collected from Pangandaran, Yogyakarta, and Lombok, Indonesia. Analyses included proximate composition, amino acid profiling, phytochemical screening, heavy metal contamination, microbiological quality, color stability, sensory evaluation, and shelf-life estimation. A seaweed-based seasoning was formulated using Lombok samples without synthetic flavor enhancers. The formulated product demonstrated a favorable nutritional composition, containing 8.67 % protein, 20.78 % dietary fiber, and 59.21 % carbohydrates. High concentrations of L-glutamic acid (53,109.10 mg/kg) and L-aspartic acid (5,772.20 mg/kg) contributed to its umami taste. Phytochemicals, including flavonoids, phenolics, saponins, and alkaloids, were detected. Hg, Pb, As and microbiological parameters met food safety standards, raw material Cd exceedance limits direct use of some sites. The product exhibited strong green (a* = –10.96) and yellow (b* = 9.99) color attributes and an estimated shelf life of 9.23 months when packaged in metallocene film. Sensory evaluation indicated high consumer acceptability, particularly when applied to potato- and Chitato Lite-based snacks.Overall, Under the tested parameters, the product complied with selected regulatory limits; however, broader batch validation is required. Further research should focus on scale-up processing and the exploration of broader food applications.